2015
DOI: 10.3389/fncel.2015.00368
|View full text |Cite
|
Sign up to set email alerts
|

Neto2-null mice have impaired GABAergic inhibition and are susceptible to seizures

Abstract: Neto2 is a transmembrane protein that interacts with the neuron-specific K+-Cl− cotransporter (KCC2) in the central nervous system (CNS). Efficient KCC2 transport is essential for setting the neuronal Cl− gradient, which is required for fast GABAergic inhibition. Neto2 is required to maintain the normal abundance of KCC2 in neurons, and increases KCC2 function by binding to the active oligomeric form of this cotransporter. In the present study, we characterized GABAergic inhibition and KCC2-mediated neuronal c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 53 publications
(91 reference statements)
0
34
0
Order By: Relevance
“…However, the greater magnitude of uIPSC property changes observed in Neto mutants compared to KAR antagonism leaves open the possibility that Netos may influence CCK/CB1 interneuron presynaptic function independent of KARs. Though Neto2 associates with and regulates surface expression of KCC2 (Ivakine et al, 2013; Mahadevan et al, 2015) any potential confounding influence by such regulation on sIPSC/uIPSC properties was avoided by directly controlling postsynaptic chloride gradients and providing large chloride driving forces to maximize signal to noise ratios for synaptic currents. Moreover, the normal gamma oscillations observed in Neto2KOs argue against a catastrophic breakdown in postsynaptic GABAergic signaling.…”
Section: Discussionmentioning
confidence: 99%
“…However, the greater magnitude of uIPSC property changes observed in Neto mutants compared to KAR antagonism leaves open the possibility that Netos may influence CCK/CB1 interneuron presynaptic function independent of KARs. Though Neto2 associates with and regulates surface expression of KCC2 (Ivakine et al, 2013; Mahadevan et al, 2015) any potential confounding influence by such regulation on sIPSC/uIPSC properties was avoided by directly controlling postsynaptic chloride gradients and providing large chloride driving forces to maximize signal to noise ratios for synaptic currents. Moreover, the normal gamma oscillations observed in Neto2KOs argue against a catastrophic breakdown in postsynaptic GABAergic signaling.…”
Section: Discussionmentioning
confidence: 99%
“…, Mahadevan et al . ), we have previously demonstrated that changes in E GABA can be detected using whole‐cell recordings (Ormond and Woodin, , Ormond and Woodin, , Takkala and Woodin, , Mahadevan et al . ).…”
Section: Resultsmentioning
confidence: 99%
“…IPSCs were evoked with a stimulating electrode placed in the stratum lucidum/radiatum when recording in whole-cell mode with a holding potential of −70 mV. Although gramicidin-perforated patch clamp recordings are often used to record E GABA , including in our own studies (Acton et al 2012, Ivakine et al 2013, Mahadevan et al 2014, Mahadevan et al 2015, we have previously demonstrated that changes in E GABA can be detected using whole-cell recordings (Ormond and Woodin, 2009, Ormond and Woodin, 2011, Takkala and Woodin, 2013. The use of the whole-cell technique was necessary in the present study as a result of the longer-term nature of the recordings, which required the washing-in and -out of pharmacological agents, and the need to include a pharmacological agent in the recording pipette.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations